CORPORATE GOVERNANCE AS A MODERATING VARIABLE INFLUENCE OF STOCK TURNOVER, EXTENSIBLE BUSINESS REPORTING LANGUAGE AND AUDIT QUALITY ON INFORMATION ASYMETRIES - Simanjuntak, Arthur; Situmorang, Christina Verawaty; Elisabeth, Duma Megaria; Ginting, Mitha Christina; Sagala, Lamria (Sekolah Tinggi Ilmu Ekonomi Sultan Agung, 2023)
The purpose of this study was to determine the role of corporate governance as a moderating variable effect of stock turnover, extensible business reporting language and audit quality on information asymmetry. The population of this research is all companies in the retail sector that are listed on the IDX for the 2019-2021 period, totaling 25 companies. The sample of this study adopted a purposive sampling method, so that the samples taken were 11 companies. The analysis technique used in this research is panel data regression analysis and moderation test. The results showed that stock turnover and extensible business reporting language had a significant positive effect on information asymmetry. On the other hand, audit quality has no significant effect on information asymmetry. Simultaneously, stock turnover, extensible business reporting language, and audit quality have a significant effect on information asymmetry. The role of corporate governance can strengthen the effect of stock turnover on information asymmetry. The role of corporate governance can weaken the extensible business reporting language against information asymmetry. Meanwhile, the role of corporate governance is not able to moderate audit quality on information asymmetry.Keywords: Stock Turnover, Extensible Business Reporting Language, Audit Quality, Information Asymmetry, Corporate Governance.